Características de tomate producido con agua tratada en interior y exterior de invernadero - Pacco, Honorato C. (2014)
The objective of this research was to determine the yield and postharvest quality of tomato "Dominador" produced inside and outside the greenhouse, irrigated by the system of surface and subsurface drip with wastewater and natural water. The experimental design was a randomized block 3x2, the portions being formed by the water quality (wastewater, water for conventional fertigation and natural water), with four repetitions. There was no significant effect of cultivars within and outside the greenhouse on the productivity index, fruit size and quality, except in the ratio of soluble solids/titratable acidity, where the highest value (2.46) was for growing inside the greenhouse, and significant increases (102%) during the storage period (fourteen days), indicating a superior quality during the storage period. The pH of the fruits produced within the greenhouse ranged from 3.95 to 4.31, and values for tomatoes produced outside the greenhouse ranged from 4.00 to 4.22 in pH during the storage. The soluble solids increased and titratable acidity was reduced during the storage period for all treatments. The tomato had shelf-life of seven days for all treatments in both cultivation environments, and stored at 27°C and 60% relative humidity.